The Role of Strategic Management Accounting for Startups in Implementing Sustainable Development Goals in PT Oesodo Alam Mandiri - Yanuar RAMADHAN; Erna SETIYAWATI; Ratna Dewi SARI; Maria IZA; Noviyanti ALAWIYAH (International Journal of Environmental, Sustainability, and Social Science, 2023)
PT Oesodo Alam Mandiri (PT OAM) is a company engaged in the partnership business that specifically provides delicious and contemporary herbal products through booths or cafes and the like by using the herbal medicine partnership business model in the form of a business opportunity. This study aims to analyze and find out how PT OAM's management strategy accounting can contribute to the implementation of the Sustainable Development Goals (SDGs) in Indonesia. The method used in this observation is a literature study by finding and using relevant theoretical references that serve as the basis and reference for finding solutions to cases or problems found. The results showed that SDGs no. 8 and 3 can be achieved by establishing a herbal medicine partnership strategy by collaborating with the Bekasi City Government to reduce the unemployment rate through the MSME program